Interoception in adolescence: Evidence from multidomain self-report of bodily sensations and cardiac behavioral measures - Silvia Canino; Valentina Torchia; Erica Dolce; Irene Ruffo; Teresa Iona; Simona Raimo; Liana Palermo (PLoS ONE, 2026)
Interoception, the sense of inner bodily signals, plays a key role in emotional regulation, cognition and mental health. While its relevance in adulthood has been extensively explored, less is known about how interoceptive  abilities develop during adolescence, a period characterised by significant physical and psychological changes. This study aimed to investigate different interoceptive dimensions in adolescents and adults to better understand the developmental profile of this sense. Fifty-four adolescents (aged 12–14) and 50 adults (aged 25–34) completed the Heartbeat Counting Task (HCT) to assess their actual ability to detect heartbeats, their confidence in this ability, and the confidence-accuracy correspondence, and a questionnaire on the tendency to focus on different bodily sensations. The study also examined where participants localised bodily sensations during the HCT. No clear group differences emerged in the accuracy during the HCT. Also, both age groups exhibited similar body localisation patterns, primarily focusing on the chest during heartbeat detection. However, adolescents showed significantly lower metacognitive awareness of their ability to perceive cardiac signals, and higher focus on interoceptive sensations, as reflected in their higher confidence ratings in the HCT and elevated scores on a questionnaire assessing the perceived frequency of internal bodily sensations. There were no significant correlations among the interoceptive measures in either group, suggesting that they may capture partially distinct aspects of interoceptive functioning and contributing to the ongoing debate on how interoceptive dimensions should be conceptualized and measured. Overall, these findings suggest that, while basic interoceptive detection may be established by early adolescence, the capacity to accurately reflect on these internal sensations continues to mature into adulthood, at least for what attains the cardiac domain. Also, the mismatch observed between adolescents’ heightened bodily focus and their limited metacognitive insight may partly help explain why adolescence is a period of increased vulnerability to mental health difficulties.